Nekovinski materiali - Anžel, Ivan; Zupanič, Franc; Brunčko, Mihael (2025)
Non-Metallic Materials. In the script Non-Metallic Materials, students will explore the key aspects of the importance of non-metallic materials in modem engineering. These materials have become indispensable in many industries for designing and manufacturing products and, in some cases, are even fully replacing metals and alloys. The unique combination of their properties enables the development of technologically advanced solutions that are both energy-efficient and environmentally friendly. With the script Non-Metallic Materials, students will gain an indepth understanding of the structure, properties, and manufacturing technologies of polymeric, ceramic, and composite materials.
Keywords: non-metallic materials; polymers; ceramics; composites; structure; properties